Designing a Sustainable Human Resource Management Model for Faculty Members of Iraqi Universities - Jassim Al-Nadher, Mohammad Amer; Farahi, Mohammad Mahdi; Maharati, Yaghoub; Eslami, Ghasem (Digital Transformation and Administration Innovation, 2025)
Sustainable human resource management is one of the most recent paradigms in human resource management that has received attention over the past two decades. The present study aimed to design a sustainable human resource management model for faculty members of Iraqi universities. This research was qualitative in nature and based on the interpretive paradigm, implemented using the systematic grounded theory approach. Through purposive sampling, 10 Iraqi experts were selected and interviewed in-depth. The resulting data were analyzed through three stages of open, axial, and selective coding, leading to the extraction of 192 final open codes. The open codes were categorized into 48 subcategories and 20 main categories. The study's paradigmatic model was designed with the following sections: contextual factors (global sustainability contexts, national sustainability contexts, and higher education sector-specific contexts); causal conditions (increasing public awareness and concern, and the importance of sustainability in achieving competitive advantage); intervening conditions (organizational culture and leadership, and availability of sufficient resources); core phenomenon or sustainable human resource management practices in universities (including sustainable recruitment and hiring, sustainability training and training in a sustainable manner, sustainable performance management, sustainable rewards and benefits, and provision of appropriate work arrangements); strategies (aligning university goals with sustainable development goals, developing a comprehensive university sustainable human resource strategy, implementing university sustainable human resource strategies and policies, overcoming individual resistance to change, promoting research in the field of sustainability, engaging stakeholders, integrating sustainability into university curricula, and sustainability performance reporting); and consequences (enhanced sustainable performance, improved status of faculty members, enhanced university reputation, and facilitation of sustainable community development).